The impact of top management support, perceived justice, supplier management, and sustainable supply chain management on moderating the role of supply chain agility - Men, Feng; Yaqub, Rana Muhammad Shahid; Yan, Rui; Irfan, Muhammad; Haider, Ali (Frontiers in Environmental Science, 2023)
Sustainable supply chain management (SSCM) is a new area of interest to scientists and industrial practitioners through which to maintain productivity, reduce costs, and enhance agility. SSCM is especially important to protect the environment and reduce pollution by heavy industries. It considers the environment the main stakeholder in minimizing the carbon footprint during production, lowering emissions of dangerous gases, and reducing industrial pollution. Considering the aforementioned purposes, the aim of this study was to explore the relationships between top management support, perceived justice, supplier management, and SSCM and assess the moderating role of supply chain agility. This quantitative study was conducted in the vast textile sector in Pakistan. We collected data through a questionnaire and found that top management support, perceived justice, and supplier management are positively and significantly associated with SSCM. However, there was no significant moderating effect of supply chain agility on the independent variables and SSCM. These findings have practical implications for production managers and top management in enhancement of their roles in promoting environmental wellbeing. By developing rules at the organizational and governmental levels that consider the role of top management, perceived justice, and improved supplier management, the sustainability of the supply chain can be improved. This analysis provides academics who study the supply chain a practical prescription and adds to the body of knowledge about the validity of top SSCM pillars.